'Finding beauty' in French rural prisons. How prison officers operate rurality - Herzog-Evans, Martine; Thomas, J (International Journal of Rural Criminology, 2021)
The literature on rural criminology and rural prisons has so far essentially focused on debunking myths about rurality and rural crimes, and on the economic and social impacts of building prisons in rural areas. Typically, such rural prisons are recent. Conversely, due to its long history, France's rural prisons have in some cases been built during the 19th century within former convents from the Middle Ages or monasteries confiscated from the church during the 1789 Revolution. Missing from this literature, therefore, is, on the one hand, a focus on historic rural prison settings and, on the other hand, attention to individuals and professionals who work there. This paper focuses on a high security prison set in a middle-ages abbey in the middle of nature. In our interviews with its prison officers (POs) we used appreciative inquiry in order to better uncover the positive dimensions of rurality. We find that rurality is used to reinforce safety and the 'right distance' with prisoners, and to better cut off from the prison environment when they finish their shift. We also find that POs are bound by strong (rural) family ties that in turn contribute to their professional identity and values, and to their feelings of safety.